2007
DOI: 10.1002/chin.200741016
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Y2O2(CN2) and Luminescence Properties of Y2O2(CN2):Eu.

Abstract: Yttrium I 2600 Synthesis of Y2O2(CN2) and Luminescence Properties of Y2O2(CN2):Eu. -The title compound is prepared by solid state reaction of different mixtures of YCl 3 and/ or YOCl and/or Y2O3 and Li2(CN2) at 620-650°C. These reactions yield trigonal Y2O2(CN2) (space group R3m1, Z = 1; powder XRD), while hexagonal Y2O2(CN2) (P63/mmc, Z = 2) is obtained from the reaction of a YCl3/Y2O3 mixture with KOCN. The structure of the trigonal modification is closely related to that of Y2O2S, where linear N-C-N units r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…Photochemical activities of cobalt and copper carbodiimides have also been reported, and the former exhibited high photocatalytic water oxidation activity under irradiation by visible light [28,29]. Alkaline earth metal and rare-earth metal carbodiimides have also been applied as host materials for doping of photoluminescence centers such as Eu 2+ , Eu 3+ , Ce 3+ , and Mn 2+ [22,23,[30][31][32][33]. A divalent Eu-doped tetragonal BaNCN red phosphor exhibits a large shift in the luminescence wavelength depending on both temperature and applied pressure, since the tetragonal phase has a flexible framework and the crystal field splitting of the 5d energy levels of the Eu 2+ ions varies depending on the bond length [23,34].…”
Section: Introductionmentioning
confidence: 99%
“…Photochemical activities of cobalt and copper carbodiimides have also been reported, and the former exhibited high photocatalytic water oxidation activity under irradiation by visible light [28,29]. Alkaline earth metal and rare-earth metal carbodiimides have also been applied as host materials for doping of photoluminescence centers such as Eu 2+ , Eu 3+ , Ce 3+ , and Mn 2+ [22,23,[30][31][32][33]. A divalent Eu-doped tetragonal BaNCN red phosphor exhibits a large shift in the luminescence wavelength depending on both temperature and applied pressure, since the tetragonal phase has a flexible framework and the crystal field splitting of the 5d energy levels of the Eu 2+ ions varies depending on the bond length [23,34].…”
Section: Introductionmentioning
confidence: 99%
“…The RE 3+ cations are coordinated with 4 oxygen and 3 nitrogen atoms in trigonal lattice . All the homologous Ln 2 O 2 (CN 2 ) (Ln = La, Y, Gd, Dy, Ho, Er, Tm, and Yb) compounds were synthesized following the solid‐state metathesis method or sol–gel method, and their crystal structures have been reported as tetragonal for Ln = La and trigonal for Ln = Ce, Pr, Nd, Sm, Eu, and Gd . It has been reported that La 2 O 2 CN 2 is an excellent matrix for RE 3+ luminescence .…”
Section: Introductionmentioning
confidence: 99%